JUSTICE IN MANY ROOMS IN SHARIA BANKING DISPUTE RESOLUTION TO ACHIEVE JUSTICE - Nita Triana; Deddy Purwinto (Fakultas Hukum, Universitas Diponegoro, 2018)
This paper examines the dispute resolution of Sharia Banking. The method is a non-doctrinal legal research using qualitative research and Socio Legal approach. Sharia banking cannot be separated from the problems between the banking and the Customer. This problem is calledproblematic financing. The resolution of problematic financing of sharia banks in litigation is now the absolute authority of the Religious Courts. The downside of litigation settlement usually takes a long time, the need for proof, the cost is quite expensive and the result is winningor lost. Therefore, the settlement of sharia banking is very rarely resolved through litigation. Alternative Dispute Resolution is a choice of dispute settlement chosen by Sharia Banking. The first stage isto carry out negotiation between all parties, namely Banking (lender) and The Customer (Debtor) in the form of warning and guidance. If it does not succeed, there will bedebt restructuration. The second step is mediation, in the form of consultation with third party as a mediator. The mediation determines the rescue process of debt by Banks when a debtor is still unable to return his debt, executed by the bank. According to Marc Galanter these various dispute resolutionsis called justice in many rooms. In Islamic Law it is known as Sulh (peace). However, to a large extent this non-litigation settlement is more satisfactory to both parties in resolving the dispute because it senses fairness and a win-win solution.